CHILD TRAFFICKING FOR SEXUAL EXPLOITATION - Gupta, Kritika; Gupta, Meenu (International Journal of Psychosocial Rehabilitation, 2020)
The current systematic review determined the reason associated with child trafficking. Moreover, to address the question that “what makes minors (including females and kids) more vulnerable to trading”? Further, the current study would determine the prevention efforts at the individual and government level to upgrade the life quality of victims. International Labour Organization (ILO) guesstimates approximately 1.2 million kids are marketed on every year.Further, 21 million adults and kids are confined to force slavery. Out of that, one in five is below 18 years of age. Children trafficking have been recognized as a grave crime that occurs worldwide. From the past few decades, the ramification and pervasiveness of this cruel act have increased to international eminence because of a dramatic rise in public and research action.Various elements can tip to the children vulnerability for commercial sexual abuse and trading and these reasons can be classified as family associated risk, children specific risk, socio-economic associated risk and environment allied risk reasons (Greenbaum, Dodd, M., & McCracken,2018).An effective technique is to find out the root cause to minimize the risk factors. Moreover, imparting education at school and society level would be an effective procedure. This study has been conducted to bridge the literature gap in children trafficking. The current review was accomplished by undertaking a thorough literature review. The data was collected through Science Direct, CINHAL Full Text, MedLine Full Text, The Cochrane, PubMed and Embase. Innumerable elements can tip to the children susceptibility for profitable sexual mishandling and trading and these reasons can be classified as family associated risk, children specific risk, socio-economic associated risk and environment allied risk reasons.Awareness programs at the community level and pamphlets distribution on trafficking would be helpful in the prevention of trading. State policies should be clear ad loud against the culprits. Moreover, laws should be strict against criminals.